2008
DOI: 10.3171/jns/2008/108/6/1211
|View full text |Cite
|
Sign up to set email alerts
|

Initial management of hydrocephalus associated with Chiari malformation Type I–syringomyelia complex via endoscopic third ventriculostomy: an outcome analysis

Abstract: Endoscopic third ventriculostomy provides a durable method of treatment for hydrocephalus associated with CM-I. It is effective as a primary treatment, and the authors advocate its use as a replacement for routine ventriculoperitoneal shunt insertion in these patients. Management of the hydrocephalus alone is often sufficient and may obviate decompression, although a significant proportion of patients will still need both procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 27 publications
3
36
4
Order By: Relevance
“…Several authors [37,[75][76][77] have reported that hydrocephalus in Chiari patients can be treated with ETV and that the success rate of this treatment can be as high as 50%. The success rate in our series was 40%, which is within the range of rates that have been described in international series.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors [37,[75][76][77] have reported that hydrocephalus in Chiari patients can be treated with ETV and that the success rate of this treatment can be as high as 50%. The success rate in our series was 40%, which is within the range of rates that have been described in international series.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent outcomes and high long-term success rates ranging from 60 to 100% have been reported in both adult and pediatric series of OHC [2,3,4,5,6,7,9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. Our 81.6% overall success rate is thus comparable to those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…ETV is currently considered by many authors the treatment of choice for OHC [1,2,3,4,5,6,7,8,9,10]. Excellent outcomes and high long-term success rates ranging from 60 to 100% have been reported in both adult and pediatric series of OHC [2,3,4,5,6,7,9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants presenting by hydrocephalus are not suitable applicants for ETV as they have not well-established absorptive surfaces in the subarachnoid spaces and have an open anterior fontanelle, with a lax skull (6,44). Yet, the ETV has been tried by numerous writers in infants with hydrocephalus, due to variable etiologies.…”
Section: Endoscopic Third Ventriculostomy Indicationsmentioning
confidence: 99%